METHODOLOGICAL BASIS FOR DETERMINING MANAGEMENT STRATEGIES INVENTORY FROM THE PERSPECTIVE OF LOGISTICS - Koretska, S. O. (Science and Transport Progress, 2006)
The article represents a methodical kit, allowing for quantitative estimation, analysis and prognostication of different options for forming the strategy of the logistic inventories control system at an enterprise.